Histopathologic evaluation of atypical neurofibromatous tumors and their transformation into malignant peripheral nerve sheath tumor in patients with neurofibromatosis 1—a consensus overview - Miettinen, Markku M.; Antonescu, Cristina R.; Fletcher, Christopher D.M.; Kim, Aerang; Lazar, Alexander J.; Quezado, Martha M.; Reilly, Karlyne M.; Stemmer-Rachamimov, Anat; Stewart, Douglas R.; Viskochil, David; Widemann, Brigitte; Perry, Arie (Human pathology, 2017)
Patients with neurofibromatosis 1 (NF1) develop multiple neurofibromas, with 8% to 15% of patients experiencing malignant peripheral nerve sheath tumor (MPNST) during their lifetime. Prediction of transformation, typically from plexiform neurofibroma, is clinically and histologically challenging. In this overview, after a consensus meeting in October 2016, we outline the histopathologic features and molecular mechanisms involved in the malignant transformation of neurofibromas. Nuclear atypia alone is generally insignificant. However, with atypia, loss of neurofibroma architecture, high cellularity, and/or mitotic activity >1/50 but <3/10 high-power fields, the findings are worrisome for malignancy. We propose the term “atypical neurofibromatous neoplasms of uncertain biologic potential (ANNUBP)” for lesions displaying at least 2 of these features. This diagnosis should prompt additional sampling, clinical correlation, and possibly, expert pathology consultation. Currently, such tumors are diagnosed inconsistently as atypical neurofibroma or low-grade MPNST. Most MPNSTs arising from neurofibromas are high-grade sarcomas and pose little diagnostic difficulty, although rare nonnecrotic tumors with 3-9 mitoses/10 high-power fields can be recognized as low-grade variants. Although neurofibromas contain numerous S100 protein/SOX10-positive Schwann cells and CD34-positive fibroblasts, both components are reduced or absent in MPNST. Loss of p16/CDKN2A expression, elevated Ki67 labeling, and extensive nuclear p53 positivity are also features of MPNST that can to some degree already occur in atypical neurofibromatous neoplasms of uncertain biologic potential. Complete loss of trimethylated histone 3 lysine 27 expression is potentially more reliable, being immunohistochemically detectable in about half of MPNSTs. Correlated clinicopathological, radiologic, and genetic studies should increase our understanding of malignant transformation in neurofibromas, hopefully improving diagnosis and treatment soon. •Clinical evaluation of growing neurofibromas in patients with neurofibromatosis 1 is often difficult.•We describe the spectrum of pathology in peripheral nerve sheath tumors in neurofibromatosis type 1.•While nuclear atypia alone is not decisive, loss of neurofibroma architecture and increased mitotic activity are worrisome.•An intermediate category “atypical neurofibromatous neoplasm” is proposed for borderline lesions.•Immunohistochemical studies assist in classification of problematic neurofibromatous tumors.